Does the vertical vs horizontal positioning of surfaces affect either biofilm formation on different materials or their resistance to detachment?. (March 2022) - Jha, Piyush Kumar; Dallagi, Heni; Richard, Elodie; Deleplace, Maureen; Benezech, Thierry; Faille, Christine
Abstract: In the food industry, the control of surface hygiene is a major issue. It is therefore essential to identify those parameters that can affect the bacterial contamination of surfaces and the effectiveness of hygiene procedures. Numerous studies have focused on the role of bacteria, flow arrangements or materials, but almost nothing has been reported on the possible impact of vertical or horizontal positioning of surfaces on bacterial contamination. The aim of the current study was firstly to determine the ability of bacterial species usually found in food processing lines to form biofilms on surfaces positioned vertically or horizontally and then to assess the resistance of these biofilms to detachment. The experiments were carried out using three bacterial strains ( Escherichia coli SS2, Bacillus cereus 98/4, and Pseudomonas fluorescens Pf1) that produced biofilms on glass, polypropylene and stainless steel (surface finishes 2B and 2R). We first observed that not only did the bacterial strain type impacts its ability to form biofilms (Ec-SS2 > Pf1 > Bc-98/4), but that the vertical vs horizontal position of the surface would also affect biofilm formation, probably due to the accumulation through sedimentation of bacteria on horizontal surfaces. However, the horizontally formed Pf1 biofilms were very fragile and could be partially removed by a gentle rinsing step. Lastly, no significant differences could be found in the ability to form biofilms on the different materials. The resistance to detachment to a standard rinsing process in a pilot rig was also investigated. While both strains and materials significantly affected the amount of biofilm detached, only Bc-98/4 biofilms were impacted by the surface position, with horizontal biofilms showing extreme resistance to shear forces. In conclusion, this study shows that horizontal surfaces in food environments probably represent an increased risk of contamination by bacteria frequently isolated from these environments and should be subjected to increased monitoring. Highlights: The three strains tested formed more biofilm on horizontal surfaces. Biofilm formed horizontally are sometimes more fragile, particularly for Pf1. Vertical and horizontal biofilms are highly resistant to detachment. Irrespective of strain, the highest number of CFU were detected on PP after rinsing. Most Ec-SS2 cells lose their viability during the rinsing procedure.